IMPLEMENTASI PROGRAM UNIT REAKSI CEPAT DALAM PEMELIHARAAN JALAN OLEH DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN SUMEDANG - akadun; Komala Widyaningsih Wowiling; Hafid Sidik Ansari; Rizka Handayani; Novi Widya Pratama; Rizki Auguste Rodin (LPPM UNSAP & FISIP UNSAP, 2022)
The purpose of this study was to determine the implementation of the Rapid Response Unit (URC) Program in Road Maintenance by the Public Works and Spatial Planning Office of Sumedang Regency. The research method used in this research is qualitative research. Determination of research informants, namely Social Situation Techniques. With the Head of Highways, Head of the Road and Community Reservation Section. Data collection techniques used, namely library research, and field studies consisting of observations, interviews, and documentation. While the data processing procedures in this study, namely data reduction, data presentation, conclusion drawing/verification, triangulation. Based on the results of the study, it was concluded that the Rapid Reaction Unit Program (URC) at the Public Works and Spatial Planning Office of Sumedang Regency had not yet fully run well, although in terms of size and policy objectives were clear, the size and objectives of the policy had not been implemented optimally due to lack of socialization to the community so that there are still many people who are negligent by littering so that it can cause water to evaporate and flood to the streets which will damage the roads. Human resources are still low, the available budget is limited, facilities/infrastructure are still lacking.The inhibiting factors in the Implementation of the Rapid Response Unit Program (URC) at the Sumedang Regency Public Works and Spatial Planning Service include: The distribution of information dissemination has not been disseminated evenly, the weather is sometimes unsupportive because if the weather is rainy the implementation of this program cannot be carried out, even if it is forced, the results will not be maximal and the road endurance will not be long. Facilities and infrastructure are still lacking.